The prevalence of stress-related covid19 quarantine among secondary-and-highschool students in northern Vietnam - Le Vu Thuy, Huong; Bui Van, Tung; Dang Quang, Tan; Nguyen Thi Phuong, Oanh; Tran Quynh, Anh (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objective: The study was conducted to examine the mental effects of COVID-19 quarantine on students in secondary and high schools in the North of Vietnam. Methods: The cross-sectional study was 5752 students in secondary-and-high schools involved in this study. Results: Based on stress levels, there was 25.9% of students having stress (n=1487), 10.4% of them had Mild stress level; 9.4% of them had Moderate stress level; 4.5% of them had Severe stress level and 1.6% of them had Extremely Severe stress level. Females students, students in high schools, students with divorced parents, domestic violence/fight had high risk of stress. Additionally, students, who feel isolated, usually contacted to their friends and wanted to go back to schools, were reported high risk of stress. Conclusion: Stress is one of the most common mental health which may causes suicide in young generation. During COVID-19 quarantine, the rate of stress among students increased but parents/guardians did not pay attention on it.